ANALISIS PERLAKUAN AKUNTANSI ASET TETAP MENURUT PSAP NO 7 PADA PENGADILAN MILITER III-17 MANADO - Syaefudin, Fanesa Isalia Minanda; Mandosa, Safira Amalinda; Pangemanan, Shane Anneke; Wangarry, Andreas Randy; Mustopa, Opa (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to analyze the accounting treatment of fixed assets applied to the Military Court III-17 Manado, based on the Government Accounting Standards Statement (PSAP) Number 7 concerning Fixed Asset Accounting. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, interviews and documentation related to fixed assets. Based on the data collected, the results of this study are divided into several parts: (1) recognition of assets, namely having a useful life of more than 12 months, not for sale in the entity's operating activities and acquired with the intention of being used; (2) fixed assets are measured based on acquisition cost or fair value; (3) assessment is seen from the measurement results; (4) expenditures after acquisition are made to extend the useful life or are anticipated to generate financial benefits in the future; (5) depreciation of fixed assets is carried out using the straight-line method; (6) termination and disposal of assets are carried out when their form is severely damaged and their useful life has stopped; (7) fixed assets are presented in the balance sheet financial report. Overall, the accounting treatment of fixed assets at the Military Court III-17 Manado has been implemented and is in accordance with PSAP No. 7 Concerning Fixed Asset Accounting. The results of this study are expected to be input for the Military Court III-17 Manado and other government entities in improving the understanding and quality of fixed asset accounting management, thus producing transparent and accountable financial reports. Keywords: Accounting treatment, Fixed Assets, PSAP Number 7